The Use of Distraction to Improve Episodic Memory in Ageing: A Review of Methods and Theoretical Implications. - Demonty, Manon; Coppalle, Renaud; Bastin, Christine; Geurten, Marie (Canadian Journal of Experimental Psychology / Revue Canadienne de Psychologie Expérimentale, 2023)
Healthy ageing is characterized by changes in several cognitive functions, including episodic memory and inhibition. While the age-related decrease in the ability to inhibit irrelevant stimuli is often associated with lower performance, especially in episodic memory, some studies have highlighted the boosting effect of distraction in several tasks in older adults, including episodic memory tasks related to recollection. The aim of this article is to review and compare previous studies according to specific study features and to consider the results in light of the dual-process model of recollection and familiarity that were used by the authors of the reviewed articles. This work led to the identification of two major points of comparison between the studies: the timeline of the distraction intervention and the implicit nature of the processes at play, which both allowed for different implications to the relationship with recollection. The use of distraction in memory tasks can enhance episodic memory, and especially recollective processes, due to specific actions at encoding and retrieval. These findings open the door to further investigations but also raise several questions concerning the role of implicit processes and the negative impact of distraction, for example.